2001
DOI: 10.1002/fut.2209
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the relationship between electricity and natural‐gas futures prices

Abstract: This article analyzes the relationship between electricity futures prices and natural-gas futures prices. We find that the daily settlement prices of New York Mercantile Exchange's (NYMEX's) California-Oregon Border (COB) and Palo Verde (PV) electricity futures contracts are cointegrated with the prices of its natural-gas futures contract. The coefficient of natural-gas futures prices in our model of COB electricity futures prices is not significantly different from the coefficient of gas prices in our model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 21 publications
3
60
0
3
Order By: Relevance
“…In the reduced-form world, some authors have suggested modeling power and fuels as cointegrated processes (cf. [47,18,44,74]), while others have suggested multi-commodity Lévy based models with various ways of capturing correlations between jumps and/or diffusion components. (cf.…”
Section: 4mentioning
confidence: 99%
“…In the reduced-form world, some authors have suggested modeling power and fuels as cointegrated processes (cf. [47,18,44,74]), while others have suggested multi-commodity Lévy based models with various ways of capturing correlations between jumps and/or diffusion components. (cf.…”
Section: 4mentioning
confidence: 99%
“…. , W : Conditions (20) state that, in equilibrium, if power buyers/consumers at demand market sector k in region r 2 purchase electricity from generating unit u of genco g in region r 1 , then the price the consumers pay is exactly equal to the sum of the electricity price and the unit transaction cost. However, if the electricity price plus the transaction cost is greater than the price the buyers/consumers are willing to pay at the demand market, there will be no transaction between this generating unit/demand market pair.…”
Section: Equilibrium Conditions For the Demand Marketsmentioning
confidence: 99%
“…In equilibrium, conditions (20) and (21) must hold simultaneously for all demand markets in all regions. We can express these equilibrium conditions using the following variational…”
Section: Equilibrium Conditions For the Demand Marketsmentioning
confidence: 99%
See 2 more Smart Citations